Von Matisse bis Picasso : Hommage an Siegfried Rosengart. - Rosengart, Angela; Schmalenbach, Werner; Kunstmuseum Luzern (Stuttgart : Verlag Gerd Hatje, 1988)
Bonnard, Pierre ; Braque, Georges ; Chagall, Marc ; Gris, Jean ; Hodler, Ferdinand ; Kandinsky, Wassily ; Klee, Paul ; Laurens, Henri ; Marini, Marino ; Matisse, Henri ; Miro, Joan ; Modigliani, Amedeo ; Picasso, Pablo ; Rouault, Georges ; Schwitters, Kurt ; Vuillard, Edouard
Von Matisse bis Picasso : Hommage an Siegfried Rosengart, Sommerausstellung 1988 - 50 Jahre Internationale Musikfestwochen Luzern, Kunstmuseum Luzern, 19. Juni - 11. September 1988
boek